Love Affair in the Afternoon - Citra Rosalyn Anwar (Universitas Muslim Maros, 2019)
Korean drama is one of the most interesting shows for women in Indonesia nowadays. In spite of the fact that Korean drama offers many themes and genres, one of the most popular theme is love affair between married men (pebinor) and married women (pelakor). Even thpugh both are stigmatized, the former is not quite popular as compared to the latter, indicating that pelakor is more stigmatized than pebinor. In most of the dramas, the main actor is a married man, who has an affair with another woman. Using visual material of a selected Korean drama, entitled “Love Affair in the Afternoon” (2019) which deals with an extramarital relations between a married woman and a married man, this article analyses pieces of the scenes in the drama which include dialogues, monologues, locations and symbols in 16 episodes. The study shows that